Agraphia for Kanji Resulting From a Left Posterior Middle Temporal Gyrus Lesion - Yasuhisa Sakurai; Imari Mimura; Toru Mannen (Behavioural Neurology)
Objective: To clarify whether agraphia or alexia occurs in lesions of the left posterior middle temporal gyrus.